Comprehensive Control of Sericea Lespedeza with Four Consecutive Years of Prescribed Fire During Summer - J. A. Alexander; W. H. Fick; J. Lemmon; G. A. Gatson; K C Olson (Kansas Agricultural Experiment Station Research Reports, 2018)
Objective:The objective of this study was to evaluate the effects of annual prescribed burning applied during the growing season on vigor of sericea lespedeza (Lespedeza cuneata) infesting native tallgrass range. Study Description:We burned nine fire-management units (14 ± 6 acres) at one of three prescribed-burning times: early spring (April 1), mid-summer (August 1), or late summer (September 1). Effects on sericea lespedeza were evaluated annually on July 10, October 10, and November 1. The Bottom Line:Compared to traditional spring, dormant-season burning, burning during the summer months over four consecutive years resulted in significant decreases in aerial frequency, stem length, seed production, and biomass of sericea lespedeza. Growing-season prescribed burning is an inexpensive and comprehensive means to control sericea lespedeza propagation and invasion.
Keywords: sericea lespedeza; prescribed burning